Prevalence of acute coronary syndrome among patients presenting with chest pain in a tertiary care cardiac centre - Simkhada, Rabindra; Budhathoki, Arjun; Yadav, Santosh Kumar; Neupane, Keshab Raj; Koirala, Manoj; Shrestha, Bishal; Sharma, Chitra Raj (Nepalese Heart Journal, 2022)
Background and aims: Chest pain is one of the common reason for hospital visit. Acute coronary syndrome is an important cause of chest pain. We aimed to study the prevalence of acute coronary syndrome among patients presenting with the chest pain and its association with common cardiovascular risk factors. Methods: Observational study conducted at Shahid Gangalal National Heart Centre from 20th January 2022 to 25th March 2022 enrolling 112 participants consecutively. Participants were interviewed focusing history of hypertension, diabetes, smoking and nature of chest pain. The diagnosis of participants whether it was acute coronary syndrome or not were recorded. Prevalence of acute coronary syndrome was calculated. Linear regression analysis was done to see the correlation with tested variables. Results: Mean age was 53.83±15.23 years. Seventy-five (66.96%) were male. Forty-two (37.5%) were hypertensive, 30 (26.78%) were diabetes and 26 (23.21%) were smoker. Fifty-six (50%) had nonspecific chest pain, 35 (31.25%) had atypical chest pain and 21 (18.75%) had typical chest pain. Among the participants 38 (33.93%) had acute coronary syndrome. Acute coronary syndrome showed positive correlation with age, gender, nature of chest pain, hypertension and smoking. Conclusion: Acute coronary syndrome was one of the common cause of chest pain among participants. Age, gender, nature of chest pain, hypertension and smoking showed positive correlation with it. Patients with these risk factor needs strong suspicion of acute coronary syndrome and further workup for prompt diagnosis and management.